Pengaruh Kredibilitas Sumber Dan Rerangka Pesan Pada Persepsi Risiko Konsumen - Euis Soliha (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
Marketing communication is defined as an attempt by companies to inform, persuade, and remind consumers both directly and indirectly about the products and brands that are sold (Kotler and Keller, 2009: 510). Marketers need to pay attention to the importance of the sender/source/sender/source/endorser is used in advertising. Sender/source/endorser will convey information, persuade or remind consumers about a product or service. Process with celebrity and expert endorsements influence change consumer attitudes and beliefs may be different (Freiden, 1984 as quoted by Biswas et al, 2006). Soliha and Zulfa (2009) suggests there are differences in risk perception of consumers on advertising by using celebrity endorser and expert endorser. Consumers feel the perception of lower risk with expert endorser than celebrity endorser. This indicates that the presences of the use of expert endorsers are more effective than celebrity endorsers in advertising.